2020
DOI: 10.1126/sciadv.abd2408
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the algal CO 2 -fixing organelle, the pyrenoid, is guided by a Rubisco-binding motif

Abstract: Approximately one-third of the Earth’s photosynthetic CO2 assimilation occurs in a pyrenoid, an organelle containing the CO2-fixing enzyme Rubisco. How constituent proteins are recruited to the pyrenoid and how the organelle’s subcompartments—membrane tubules, a surrounding phase-separated Rubisco matrix, and a peripheral starch sheath—are held together is unknown. Using the model alga Chlamydomonas reinhardtii, we found that pyrenoid proteins share a sequence motif. We show that the motif is necessary and suf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 50 publications
6
86
0
1
Order By: Relevance
“…In eukaryotic microalgae, liquid-like Rubisco-EPYC1 (Essential Pyrenoid Component 1) condensates display functional similarity to Rubisco-CcmM condensates, they are found compartmentalized in an analogous chloroplastlike CCM compartment called the pyrenoid (Figure 3B; The pyrenoid matrix is predominantly composed of Rubisco-EPYC1 complexes, forming by the multivalent interactions of EPYC1 peptide (orange) and Rubisco (green and yellow) (Freeman Rosenzweig et al, 2017;Wunder et al, 2018;Meyer et al, 2020;Barrett et al, 2021). Cryo-EM supported a structural model (7jsx, He et al, 2020), showing that EPYC1 binds close to the equator of the Rubisco cylinder and forms a codependent network of the specific low-affinity bonds (Mackinder et al, 2016;He et al, 2020).…”
Section: Enhancing Activities By Concentrating Enzymes and Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In eukaryotic microalgae, liquid-like Rubisco-EPYC1 (Essential Pyrenoid Component 1) condensates display functional similarity to Rubisco-CcmM condensates, they are found compartmentalized in an analogous chloroplastlike CCM compartment called the pyrenoid (Figure 3B; The pyrenoid matrix is predominantly composed of Rubisco-EPYC1 complexes, forming by the multivalent interactions of EPYC1 peptide (orange) and Rubisco (green and yellow) (Freeman Rosenzweig et al, 2017;Wunder et al, 2018;Meyer et al, 2020;Barrett et al, 2021). Cryo-EM supported a structural model (7jsx, He et al, 2020), showing that EPYC1 binds close to the equator of the Rubisco cylinder and forms a codependent network of the specific low-affinity bonds (Mackinder et al, 2016;He et al, 2020).…”
Section: Enhancing Activities By Concentrating Enzymes and Substratesmentioning
confidence: 99%
“…Cryo-ET also showed that both the algal EPYC1 and cyanobacterial CcmM bind close to the equator of the Rubisco cylinder ( Wang et al, 2019 ; He et al, 2020 ), although the binding sites are different. Specifically, EPYC1 binds uniquely to the Rubisco small subunit (RbcS) via electrostatic and hydrophobic interactions ( Figure 3B ; He et al, 2020 ; Meyer et al, 2020 ), while CcmM contacts both Rubisco large subunit (RbcL, Wang et al, 2019 ) and RbcS via salt bridges and van der Waals contacts ( Figure 3A ). Both EPYC1 and CcmM have repeat regions and intrinsically disordered proteins, and as has been side, the Rubisco condensation events appear to be regulated in a similar multivalent mechanism.…”
Section: The Biological Function Of Phase-separated Condensates In Microorganismsmentioning
confidence: 99%
“…Recent work in the model green alga Chlamydomonas reinhardtii (hereafter Chlamydomonas) has shown that the pyrenoid is a liquid-like condensate that undergoes liquid −liquid phase separation when the CCM is active 14 . Phase separation is facilitated by multivalent interactions between the intrinsically disordered Rubisco-binding protein EPYC1 and the small subunit of Rubisco (SSU) [15][16][17][18][19][20] , of which residues on the α-helices of the native SSU isoforms are critical for binding to EPYC1. Previously we have shown that Arabidopsis can assemble a functional plant-algal hybrid Rubisco complex, with the native large subunit of Rubisco (LSU) and an SSU from Chlamydomonas, which has similar kinetic properties to wild-type (WT) Arabidopsis Rubisco 21 .…”
mentioning
confidence: 99%
“…1I,J), strikingly visible as fluorescence from inside the pyrenoid, a proteinaceous structure within the chloroplast that generates a visible dip in chlorophyll fluorescence (Mackinder et al, 2017). Note that the RBCA-cTP+23 construct contains a pyrenoid-localisation motif (Meyer et al, 2020). By contrast, mitochondrial targeting peptides (mTPs) from carbonic anhydrase 4 (CAH4) and γ-carbonic anhydrase 2 (CAG2) show mitochondrial targeting, evident as co-localisation of Venus and MitoTracker fluorescence, in the absence of any post-cleavage site residues (Fig.…”
Section: Resultsmentioning
confidence: 99%